A Review of the Legal Tools for Management of Sundarban Biosphere Reserve, West Bengal, India - Dey, Sangita; Debnath, H. S.; Sikdar, P. K. (Indian Forester, 2006)
The Sunderbans Biosphere Reserve (SBR) is the largest marine biosphere reserve in India to conserve the coastal and threatened mangrove ecosystem. The importance of mangrove forests of Sunderbans in terms of international, national and local level as well as to the total economy of the country is immense. However it has been reported that for the last two decades this rich and diverse mangrove ecosystem is under continuous threat due to various natural and anthropogenic activities. To conserve this ecologically fragile environment various rules, regulations and legislations were enacted from time to time. The Indian Forest Act, 1927, is responsible for declaration of 9,630 km2 areas as Reserved Forest within the Sunderbans. The Forest (Conservation) Act, 1980, actually forms the basis of protection of forestland because it restricts use of forestland for non-forest purposes. The Wild Life (Protection) Act, 1972, provides the basis for declaration of national Parks and sanctuaries within the reserve. It also prohibits hunting and poaching of wild animals. The Environment (Protection) Act, 1986, is an umbrella act and provides protection from all the different types of pollutants. The Coastal Regulation Zone Notification (CRZ), 1991, The West Bengal Marine Fishing Regulation Act, 1993 regulates shrimp culture and marine fishing respectively. But in spite of all these legal tools and machinery the illegal trespassing, hunting discharge of various types of pollutants and unsustainable fishing are still continuing. So more stringent legal action against the defaulters by increase in penalty and imprisonment years as well as closing of polluting units in some cases are recommended. The Coastal Regulation Zone Notification (CRZ), 1991, is required to be reviewed for formulation of the Shoreline Management Plan. Also to make the legal tool stronger the identified provisions of various International Conventions should be incorporated in the legal framework on a priority basis.